KONSEP TATA USAHA RUMAH SAKIT - Ardiyanna; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
An organization requires systematic and organized records management. Records are kept to inform decision-making and policy formulation, because without information, it would be impossible for the organization to carry out its administrative activities properly and effectively. The researcher’s objective is to enhance the quality of discipline expected of workplace employees, foster honesty, creativity, perseverance, and responsibility, provide experience and socialization in the professional world, broaden perspectives, generate ideas and inspiration, and promote authenticity. The research method employed is qualitative descriptive, defined as a research procedure that generates descriptive data in the form of written words or statements from individuals observed during activities related to the research theme—in this case, the Implementation of the Records Management System in the Administrative Section of Wijaya Kusuma Hospital. The research findings reveal that the records management system used in the Administrative Subdivision of Wijaya Kusuma Hospital is a one-stop system, meaning all incoming correspondence is handled by a single unit, namely the Administrative Subdivision. For records storage in the Administrative Subdivision of Wijaya Kusuma Hospital, a classification code and index (subject matter) are utilized.